Joseph Ratzinger and Cultural Dynamisms: Insights for the Renewal of the Techno-Scientific Culture - Maurice Ashley Agbaw-Ebai (Religions)
From the Christian heartland of Europe emerged the techno-scientific culture borne from the Enlightenment movement. Prior to this cultural outlook that severed culture from its foundational roots in religion, it was the case that religion was not only a crucial agent in the shaping of culture, but in many ways, the heart of culture. With secular rationality and its underscoring of the techno-scientific mindset, a growing privatization of religion has become the acceptable ethos of contemporary Western culture. Secularism, largely understood in terms of a naked public sphere, is increasingly perceived to be the only form of rationality that can guarantee societal cohesion and the democratic spirit. But as Ratzinger pointed out in his 1993 Hong Kong Address to the Doctrinal Commissions of the Bishops Conferences of Asia, this Western understanding of culture that is governed by a hermeneutic of suspicion towards religion, and which seeks to replace the heart of culture with autonomous reason a la Kant, ends up leaving culture in a winter land of existential frostiness. By depriving culture of its roots in the transcendental dimensions of human experience, much of the wisdom and riches that have been accumulated in the pre-techno-scientific cultures—regarding fundamental questions such as “Who am I?”, “Why am I here?”, “What is the meaning of life?”, “What happens when I die?”, “Does life make sense?”, “Do I have a destiny?” and more—are now left to the manufactured logic of the techno-scientific with its anthropological reductionism that fails to offer the big picture of the cultural outlook that did not construe the scientific and the technological as antithetical to religion. This essay seeks to unpack the arguments Ratzinger made in this Address at Hong Kong, with the hope that this theological exegesis of the Hong Kong lecture could once again offer an invitation to the world of the techno-scientific, the world of secular rationality, to open up to the world of faith, so that together, the breadth and depth of the human culture would once again flourish in its greatness.